Investigating the visible range photoresponse of an organic single-crystal analogue of the green fluorescent protein - Virole, Vishal; Dabke, Niteen; Verma, Sahil; Kumar, Ajay; Pandya, Rinu; Husale, Sudhir; Vanka, Kumar; Gonnade, Rajesh; Kanawade, Rajesh (Nanoscale, 2025)
The growing demand for lightweight, flexible, semi-transparent and low-cost photodetectors (PDs) in wearable electronics and optical communication systems has prompted studies to investigate organic materials as feasible alternatives to conventional inorganic PDs. However, modern organic PDs often face responsivity, detectivity, and photoresponse speed limitations, particularly in the visible range. Here, we present the photoresponse of an organic single-crystal analogue of the green fluorescent protein (GFP) chromophore photodetector, fabricated on a silicon nitride substrate. A significant increase in photocurrent was detected upon illumination with visible wavelengths (532 nm, 630 nm, and halogen light). A remarkably consistent and repeatable photoresponse was obtained during the ON and OFF illumination cycles. The device showed the dependence of photocurrent on the applied bias voltages. The measured photocurrent, responsivity, detectivity, rise time, decay time, noise equivalent power and external quantum efficiency are studied for different wavelengths. Strikingly, the fabricated device demonstrates excellent performance in the visible region compared to several conventional organic and inorganic PDs. The observed responsivity and detectivity values for the device are 98 mA W-1 and 7.94 x 108 Jones, respectively. Furthermore, the device also exhibits rapid photoresponse dynamics with a rise time of 180 ms and a decay time of 152 ms. The excellent photodetection features indicate that the single crystal GFP could serve as a versatile broadband material for future applications in optoelectronics.